About social innovation: epistemological, technical, theoretical and methodological considerations on the academic production from 2008 to 2012 - Menelau, Sueli; Adaid-Castro, Breno Giovanni (Revista de Administração da UFSM, 2018)
The present work aimed to delimit the concept of social innovation in its epistemological aspects, theoretical, technical and morphological to support studies on innovations that seek social results. The review of the production, from January/2008 to January/2013, it’s noted that the theme has been studied thought different biases in the Business Administration area, which is mostly defined by the Quadrupole analysis of Social Innovation. Findings indicates that the result of actions of organizations and persons being it to solve a problem, develop a new economic or social benefit is the current definition of Social Innovation. This understanding acted as a stimulus to propose a research agenda to build and develop a more consistent understanding of the concept of Social Innovation and determine whether the creation and dissemination of Social Innovation has a relation with the creation of risk and more perceived social value.